2023
DOI: 10.1002/ar.25335
|View full text |Cite
|
Sign up to set email alerts
|

The osteology of the Late Triassic reptile Scleromochlus taylori from μCT data

Davide Foffa,
Sterling J. Nesbitt,
Richard J. Butler
et al.

Abstract: Scleromochlus taylori is one of the most enigmatic members of the herpetofauna from the Lossiemouth Sandstone Formation (Upper Triassic) of Elgin (Moray, Scotland). For many years it was thought to be closely related to pterosaurs and dinosaurs, but the anatomy of this animal is difficult to interpret because of the notoriously poor preservation of the six available specimens, which comprise void space in the sandstone after the bones were destroyed by diagenesis. Historically, these fossils have been studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 87 publications
(401 reference statements)
0
2
0
Order By: Relevance
“…Recent studies have demonstrated the close relationship between pterosaurs and lagerpetids, elucidating one of the most interesting macroevolutionary processes in vertebrate history. In this context, Foffa et al (2024, this issue) provide the thus far most detailed description of the iconic avemetatarsalian Scleromochlus taylori . Classically considered a key player in the origin of pterosaurs (and dinosaurs), the small reptile is recovered by the authors as a member of Lagerpetidae, indeed contributing to the understanding of the early evolution of Pterosauromorpha.…”
Section: Figurementioning
confidence: 99%
“…Recent studies have demonstrated the close relationship between pterosaurs and lagerpetids, elucidating one of the most interesting macroevolutionary processes in vertebrate history. In this context, Foffa et al (2024, this issue) provide the thus far most detailed description of the iconic avemetatarsalian Scleromochlus taylori . Classically considered a key player in the origin of pterosaurs (and dinosaurs), the small reptile is recovered by the authors as a member of Lagerpetidae, indeed contributing to the understanding of the early evolution of Pterosauromorpha.…”
Section: Figurementioning
confidence: 99%
“…The interpretation that Lagerpeton represented the earliest-diverging member of the dinosaur lineage was unanimously followed by subsequent authors that studied dinosaur origins (e.g., Bittencourt et al, 2015;Brusatte et al, 2010;Cabreira et al, 2016;Ezcurra, 2006Ezcurra, , 2016Irmis et al, 2007;Langer et al, 2010Langer et al, , 2013Nesbitt, 2011;Nesbitt et al, 2010;Novas, 1996). More recently, Lagerpeton and its kin (i.e., Lagerpetidae) were re-interpreted as the sister group to Pterosauria, forming the clade Pterosauromorpha with them (e.g., Baron, 2021;Ezcurra, Nesbitt, Bronzati, et al, 2020;Foffa et al, 2022Foffa et al, , 2024Kellner et al, 2022;Müller et al, 2023).…”
Section: Introductionmentioning
confidence: 98%